Cold Outbreaks at the Mesoscale in the Western Mediterranean Basin: From Raincells to Rainbands - Jordi Mazon; David Pino (Advances in Meteorology)
This paper investigates cold outbreaks that form offshore density currents within the whole mesoscale over the Western Mediterranean basin. Reflectivity radar and satellite images are used to detect clouds and precipitation that are associated with these density currents in the meso-α, meso-β, and meso-γ over the Western Mediterranean basin (WMB). Version 3.3 of the WRF-ARW model is used to describe the formation and evolution of these density currents and to estimate their lifetime as well as horizontal and vertical scales. Based on the observations and simulations, this paper suggests that a new perspective could effectively be adopted regarding the WMB region delineated by the Balearic Islands, the northeastern Iberian Peninsula, and the Gulf of Lion, where inland cold outbreaks develop into density currents that move offshore and can produce precipitation ranging from raincells to rainbands at the whole mesoscale.